Respiratory syncytial virus: presentation, treatment and prevention of a neonatal intensive care unit outbreak in Lima - Paredes, T (2012)
Respiratory syncytial virus (RSV) is the main pathogen causing lower respiratory tract infections during the first year of life and causes high rate of hospitalizations in children under 12 months. Its clinical presentation and emergence as severe outbreaks in preterm units represents high risk of morbidity and mortality. Two cases are presented and analysis of importance of early diagnosis, ventilatory management and hygienic measures is done in order to reduce hospitalization and prevent presentation of new cases in a Lima, Peru’s neonatal intensive care unit.